Application Hots-Based Discovery Learning Model to Improve Student Learning Outcomes - Damayanti, Safrida Dwi; Muhtarom, M; Purwati, Heni; Nugroho, Oky Pitoyo (Universitas Sarjanawiyata Tamansiswa, 2023)
Students' Higher Order Thinking Skills (HOTS), as seen from their learning outcomes, still need to be more optimal. This study aimed to describe applying the HOTS-based Discovery Learning model to improve student learning outcomes in curved-side geometric shapes. This research is a type of classroom action research. The subjects in this study were 9F class students at one of the public schools in Semarang. Data collection techniques are through written tests, while descriptive analysis is used. This research was conducted in 2 cycles. In cycle I, the level of completeness of students reached 57.14%, and in cycle II, the completeness reached 82.85%. The difference in mastery learning outcomes is 25.71%. From these results, using HOTS-based discovery learning is likely to improve the completeness of student learning outcomes in mathematics subject matter of curved side shapes.